Prediction of Playing Ability of Tamil Nadu Handball Players in Relation to their Motor Ability and Kinthropometric Variables of Handball Players - K. , Kathiresan; A. , Suman Kumar; Yokesh, T.P. (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the study is to find out the prediction of playing ability of Tamil Nadu handball players in relation to their motor ability and kinthropometric variables. A total of 120 subjects are selected randomly from Tamil Nadu. In the modern world. The individual characteristics may include any thoughts pertaining to the need of the game, and in the case of handball, the motor ability and anthropometric variables have no place and match for higher a many the individual characteristics each individual or team that participates in any sports events wants to win because society attracts great significance of winning. Handball being a running dribbled game, the game gained popularity and spread all over the world, and having various fundamental skills needs the factors that relate to the development of health and increase functional capacity of the body, which contributes to the successful performance of fundamental skills in handball. This will also be helpful in general in developing means of handball players and the game of handball. The results of the study set a general trend of the improvements in overall handball playing ability according to their level of competitions